Measure-and-remeasure as an economically feasible approach to crediting soil organic carbon at scale - Eric Potash; Mark A Bradford; Emily E Oldfield; Kaiyu Guan (Environmental Research Letters)
Agricultural carbon crediting predominantly relies on process-based biogeochemical models to estimate accrual of soil organic carbon stock (SOC). We investigate the conditions under which it may be economical to estimate SOC accrual by measuring and remeasuring SOC, which relies on fewer assumptions than modeling. We analyze multi-field measure-and-remeasure SOC projects with two key features: first, practice assignment is randomized to compare the effect of a treatment (e.g. no tillage) to a control (e.g. conventional tillage); second, a random subset of fields is sampled (two stage cluster sampling) to cost-effectively measure SOC changes. We use statistical modeling to characterize the estimated treatment effect, accounting for within-field and between-field variability in SOC change, as well as measurement error. We then use these statistics to evaluate how prices for measurement, treatment, and carbon credits influence the economics of measure-and-remeasure projects. We specifically investigate the potential advantages of larger spatial scale (number of fields) and temporal scale (years before remeasurement). We find economies of both spatial and temporal scale so that projects with thousands of fields, with only about 10% of fields measured for SOC change, are likely to yield a competitive return on investment in five years if the treatment effects found in the research literature can be achieved commercially. Our analysis suggests that measure-and-remeasure can be cost effective in both market and non-market SOC projects at scale. Moreover, measure-and-remeasure projects provide valuable data for independent validation on commercial farms of the accrual rates estimated by biogeochemical models using field trials. We provide next steps and software for researchers, credit registries, and project developers to move forward with measure-and-remeasure SOC projects.